Patient, disease and surgeon predictors of successful bilateral sentinel lymph node mapping for endometrial cancer: A retrospective, multicenter analysis - Towner, Mary; Underkoffler, Kaylee; Urh, Anze; Robison, Katina; Moore, Richard G (Clinical Journal of Obstetrics and Gynecology, 2022)
Objective: Sentinel lymph node mapping is an acceptable standard for lymph node evaluation in patients with endometrial cancer. The purpose of this study was to evaluate the adoption of this technique at two academic institutions, including which patient and disease features are associated with rates of successfully identifying sentinel lymph nodes with fluorescent mapping. In addition, we sought to characterize if and how surgeons experience the technique related to successful bilateral sentinel lymph node mapping. Methods: A retrospective chart review was performed of patients at two academic institutions who underwent sentinel lymph node mapping prior to a minimally invasive hysterectomy for endometrial cancer over the first 30 months during which the technique was adopted at each institution. A modified Poisson regression model was used to determine the relationships between patient, disease, and surgeon factors on outcomes of sentinel lymph node mapping. Results: A total of 460 charts were reviewed. The mean age was 64 and the median body mass index was 34.2. The most disease was stage I (83%), endometrioid (89%), and Grade I (64%). The bilateral sentinel lymph node mapping success rate was 65%, while unilateral or bilateral success occurred in 91% of cases. Sentinel lymph node mapping was significantly more likely to be successful in premenopausal women (RR 1.25; 95% CI 1.07 - 1.46; p = 0.005) and Asian women (RR 1.48; 95% CI 1.3-1.68; p < 0.001). BMI was not significantly predictive of mapping success (RR 1.03; 95% CI 1.00 - 1.07; p = 0.05). Increasing surgeon experience with the technique did predict successful bilateral sentinel lymph node mapping (RR 1.02; 95% CI 1.00 - 1.03; p = 0.02). Conclusion: Premenopausal status and surgeon experience with the technique increases the likelihood of bilateral sentinel lymph node detection for endometrial cancer.